A Study On Restaurant Waste At Feni Town - Akbar, Md Ali; Nath, Partha Pratim; Oni, Sajedul Islam; Hosen, Emam (Feni University Journal, 2026)
This study identified the key reasons for food waste production and management in restaurants in Feni Town with a view to understanding the waste management of this city. This had been conducted using a mixed-methods research design. 20 Restaurants from the busiest areas of Feni Town served as the study's research population. The information was gathered through a questionnaire survey, observation, and conversations with restaurant workers and owners. According to the study's findings, almost 7.15% of prepared food was wasted each day and more than 50% of this wasted food was from customers' plates. Other causes of waste include poor food storage, haphazard arrangement of raw ingredients, waste that occurs during cooking, and portion size. A survey found, 60% of leftover food was thrown away in the environment. So, effective management allows restaurants to reduce food waste, but it can be difficult to get patrons to do the same. The analysis's basic findings showed that the majority of restaurants in Feni Town are uninformed of the negative environmental effects of food waste and are doing very little to create a zero-waste establishment. Only 10% restaurants that are comparatively new provide some training to their staff about FW management. This study might be very promising for the future large scale research on restaurant waste management of poor and overpopulated countries like Bangladesh. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (53-66)